O potrzebie rekonstrukcji przestrzeni badawczej w nauce o stosunkach międzynarodowych. Refleksje natury polityczno-normatywnej, systemowej i metaforycznej - ŁOŚ-NOWAK, Teresa (Przegląd Politologiczny, 2018)
The world of the 21st century provides an intriguing space for academic reflection, offering new challenges and stimulating new concepts of international relations. In this context there emerges the significant question of the essence and direction of these concepts. They may entail deconstruction followed by a reconstruction of the research space in this field. Astrategy of resetting cannot be excluded here, either. Assuming that reconstruction is the appropriate solution there are significant issues of its scope and direction. If a total reset is considered rational we need to address the issue of what it should involve. This is a difficult question for researchers into international relations because it would mean that the hitherto achievements of this subject are being questioned. The post-positivist approach of numerous researchers, which manifests their response to the positivist methodology in the field of international relations, has not so far produced a unified methodological formula or a relatively coherent theory of international relations. Questions concerning the function of science, the nature of the social world (ontology) and the relationship between knowledge and the world (epistemology) remain open. Therefore, it may be worth going back to M. Wight’s provocative thesis that it is impossible to construct a reasonable theory of international relations, mainly owing to the dichotomy of the two fields of research that – in his opinion – cannot be overcome, namely the dichotomy of the ‘international’ (the realm of external affairs of states) and ‘internal’ (the realm of internal affairs within state), which are mutually exclusive because of their specificity; and once again ask the questions of how sensible the thesis of the dichotomy of both these environments is in a world that is strongly conditioned by the cross-border actors, interdependence and globalization. While the separateness of the ‘internal’ and ‘external’ state environments was, for Wight, an important obstacle, making it impossible to construct an academic theory explaining international relations, at the same time the current theory regarding their exclusivity in the context of the internalization of international affairs and the externalization of conditions inside states seems unsustainable. This phenomenon currently allows us to explain the imperative for combining these two environments, overlapping them …breaking down the old, established orders as a result of the now clearly visible phenomena and processes of the ‘internal state’ merging into the ‘international environment’ and vice versa, the disappearance of the traditional functions of borders, the weakening of old institutions and structures for steering the international environment as well as replacing them with entirely new institutions and structures.